Pengembangan Media Pembelajaran Kalender Sejarah untuk Meningkatkan Efektivitas Belajar Siswa Kelas 5B pada Mapel IPS di MI Roudlotut Tolabah Kabupaten Kediri - Hikmah, Dewi Malaul; Rohmawati, Aulia (Program Studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This study is motivated by the lack of student engagement in Social Studies (IPS) classes at grade 5B of MI Roudlotut Tholabah, Kediri Regency, where students remain passive, merely listening without the use of educational media, especially in Social Studies subjects. To address this issue, the study developed an educational medium in the form of a history calendar. Using a quantitative approach with R&D research following the ADDIE model, this study produced a medium that was deemed feasible by content experts (95% from lecturers and 90% from teachers), pre-test and post-test experts (100%), media design experts (85%), learning experts (87.5%), and user evaluations (84%). The study also showed that the history calendar could enhance students' learning effectiveness, evidenced by the learning effectiveness evaluation from learning experts at 83.37% and by the researcher at 81.25%, along with an average increase in scores from pre-test to post-test of 56.23%.